Pelatihan Konten Pembelajaran Kreatif dan Interaktif pada Himpunan Guru Kota Batam - Elisa, Erlin; Tukino, Tukino; Harman, Rika; Simanjutak, Pastima; Handoko, Koko; Zetli, Sri (PUAN INDONESIA, 2024)
Advances in digital technology have taken an important role in people's lives, this progress certainly provides many conveniences in increasing the intensity of work to become more effective and efficient, one of which is in the field of education, where education in fact must follow technological developments, especially in learning methods, so that it can always improve quality. learning, this service activity was held at the Teachers' Association in Batam City, which consists of kindergarten and elementary school teachers. This group of teachers still has limitations regarding what kind of interactive methods should be given to students so that they don't get bored quickly, considering that their students are included in the category of children who need something new, so far teachers have not utilized application technology to support them in provided the material, until the training was given they were still using Microsoft Office only and had not tried other media. In this activity, we from the service team will provide interactive training in creating creative learning content. On this occasion, the team will provide how to create presentations and interactive animated videos using the Powtoon application. The Powtoon application can help smart teachers explain material concepts more clearly as well as limitations. space, time and senses, especially in schools that are still implementing distance or hybrid learning methods.